IMPROVEMENT IN PERFORMANCE PARAMETERS OF A MICROSTRIP ANTENNA - Santosh Yadav (International Educational Journal of Science and Engineering, 2026)
Effect of a change in Patch geometry on the performance of a microstrip antenna is presented. The change in patch geometry is affected by inserting a V-slot and vertical identical slots on the patch. With a V-slot, the antenna resonates with four bands having bandwidths of 1.3% at 4GHz, 6% at 7GHz, 3.1% at 10GHZ and 1.07% at 13GHz. Also the return losses are -10.6117dB, -15.26dB and -16.05dB. With five identical vertical slots, the antenna resonates with four bands in which two are negligible and remaining are resonating much beyond the design frequency of 4GHz